2018
DOI: 10.1002/dys.1595
|View full text |Cite
|
Sign up to set email alerts
|

Daily motor characteristics in children with developmental coordination disorder and in children with specific learning disorder

Abstract: An association between learning disorders and coordination problems has been reported in several studies over the last few decades. In this study, we have investigated daily motor characteristics in children with a diagnosis of specific learning disorder (SLD) and compared them with those of children with developmental coordination disorder (DCD) and those of typically developing controls. Ninety-six children aged 5 to 12 years were included: 29 with a diagnosis of SLD, 33 of DCD, and 34 controls. The Italian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
1
1
0
4
Order By: Relevance
“…Se destaca la coordinación motora con resultados más expresivos. Converge con los estudios de que se centra en el desarrollo del movimiento del motor, al mismo tiempo en que ponen en juego las funciones intelectuales (Baldi et al, 2018). Corroborando con los estudios que relacionan el desarrollo motor con coordinación motora y aprendizaje.…”
Section: Profesoresunclassified
See 1 more Smart Citation
“…Se destaca la coordinación motora con resultados más expresivos. Converge con los estudios de que se centra en el desarrollo del movimiento del motor, al mismo tiempo en que ponen en juego las funciones intelectuales (Baldi et al, 2018). Corroborando con los estudios que relacionan el desarrollo motor con coordinación motora y aprendizaje.…”
Section: Profesoresunclassified
“…Los investigadores del proceso de alfabetización, que utilizan el movimiento corporal para la adquisición del desarrollo cognitivo, relatan que la dificultad en el aprendizaje, en algunos casos, se produce debido a la falta de experiencia corporal de los niños, la vida moderna, problemas psicológicos y de la convivencia social entre otros (Baldi, Caravale y Presaghi, 2018;Cardoso, Magalhães y Rezende, 2014). Además, los aspectos afectivos, sociales, económicos y culturales, también pueden ejercer influencia, provocando modificaciones en la evolución del desenvolvimiento humano (Ferreira, Godinez, Gabbard, Vieira y Caçola, 2018;Eickmann, Emond y Lima, 2016).…”
Section: Introductionunclassified
“…Além do comprometimento da função cognitiva, essas crianças comumente apresentam limitações para realizar atividades motoras grossas e finas decorrentes do déficit de equilíbrio e da coordenação motora. 7,8 A literatura aponta que crianças com DI possuem limitações motoras, principalmente em atividades relacionadas ao equilíbrio estático e dinâmico, atividades com bola e em locomoção. 9,10 Em crianças com TEA observa-se déficit de equilíbrio 11 , déficit de coordenação motora e dificuldade na preparação, planejamento, tempo e organização dos movimentos.…”
Section: Introductionunclassified
“…7,13 Já as crianças com TA geralmente apresentam déficit em coordenação motora, com menor autonomia em tarefas do cotidiano. 8 Considerando que crianças com as diferentes condições que englobam os TND apresentam comumente comprometimento da função cognitiva e a presença de limitações motoras grossas, é importante verificar se estes estão relacionados. Dessa forma, o objetivo deste estudo foi verificar se a função cognitiva está associada e pode explicar parte da variabilidade das habilidades motoras em crianças com TND entre 5 e 10 anos de idade.…”
Section: Introductionunclassified
“…Analysis conducted by Nicolson and Fawcet [27] has shown that cerebellum and procedural deficits in the neural network may be associated with specific language problems experienced by individuals with dyslexia [26]. Baldi [28] examined daily motor characteristics in 96 children aged between 5 and 12 years children with a diagnosis of specific learning disorder (SLD) and compared their performance with those of children with developmental coordination disorder (DCD) and typically developing controls. They used the Italian version of the Developmental Coordination Disorder Questionnaire to assess children's coordination in everyday functional activities.…”
mentioning
confidence: 99%